A Flipped Classroom Based Virtual Learning Prototype for Developing Undergraduates’ English Receptive Skills - Jehma, Hambalee; Prachyapruit, Apipa; Methakunavudhi, Pateep (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2024)
This quasi-experimental research aimed to develop the prototype of virtual learning implemented in flipped classrooms and evaluate its effectiveness as a tool for developing Thai undergraduates’ English receptive skills. The experimental sample group were 40 undergraduates studying English as a required general education subject at a university in Thailand. They were purposively selected as their English proficiency level did not meet the university requirement of not lower than 600 of the TOEIC scores for graduation. The actual TOEIC tests as a pre and post tests have been employed to examine if the prototype was effective. The collected data from pre and post tests were, then, analyzed through the t-Test and ANOVA. The results showed that the designed prototype applied in teaching and learning through the three online virtual platforms, namely Second Life, VRChat, and the ClassStart in the flipped classrooms were effective for developing students’ English receptive skills as the overall development of students’ English receptive skills both listening and reading shown from their post-test English TOEIC scores had significant development, showing that the post-test scores were higher than that of their pre-test’s. Thereby, applying this prototype for language teaching and learning as a pedagogy was highly advised.